ANALYSIS Of NETWORK TRAFFIC USING WIRESHARK SOFTWARE - Adkham Bozorov Norqabil ogli (American Journals Publishing, 2023)
This paper discusses the process analysis of how wireshark analyzes Ethernet computer networks.
Keywords: computer network, protocol analyzer, cloud technologies, network protocols, Sniffers.